The influence of detailed offender characteristics on consecutive criminal processing decisions in the Netherlands - Wermink, Hilde (Crime & delinquency, 2017)
Recent scholarship on sentencing disparity emphasizes the need to consider multiple decision-making points, to incorporate more detailed information on offender background characteristics, and to examine disparity in broader international contexts. This study investigates both pretrial and final sentencing decisions, incorporating a broad array of theoretically relevant offender characteristics. It combines rich survey data with official sentencing data. This data collection is part of a larger project, the Prison Project, in which 1,904 Dutch pretrial detainees were interviewed. Results indicate that several different offender characteristics exert important independent effects over criminal processing decisions and that pretrial release exerts a powerful influence over final sentencing decisions. These findings contribute to ongoing scholarly debates over the key determinants of criminal punishment in international context.